IMPROVING ACCOUNTING OF LONG-TERM BIOLOGICAL ASSETS IN AGRICULTURE (World Economics and Finance Bulletin, 2024)
This article covers the issues of accounting for long-term biological assets in agriculture. Definitions and approaches of the normative legal documents, foreign and domestic economists to the concept of biological assets have been researched. Proposals and recommendations have been developed to improve the accounting of long-term biological assets.